Faecal metabolite profiling identifies medium-chain fatty acids as discriminating compounds in IBD. Issue 3 (8th May 2014) - De Preter, Vicky; Machiels, Kathleen; Joossens, Marie; Arijs, Ingrid; Matthys, Christophe; Vermeire, Severine; Rutgeerts, Paul; Verbeke, Kristin
Abstract : Background: Bacteria play a role in the onset and perpetuation of intestinal inflammation in IBD. Compositional alterations may also change the metabolic capacities of the gut bacteria. Objective: To examine the metabolic activity of the microbiota of patients with Crohn's disease (CD), UC or pouchitis compared with healthy controls (HC) and determine whether eventual differences might be related to the pathogenesis of the disease. Methods: Faecal samples were obtained from 40 HC, 83 patients with CD, 68 with UC and 13 with pouchitis. Disease activity was assessed in CD using the Harvey–Bradshaw Index, in UC using the UC Disease Activity Index and in pouchitis using the Pouchitis Disease Activity Index. Metabolite profiles were analysed using gas chromatography–mass spectrometry. Results: The number of metabolites identified in HC (54) was significantly higher than in patients with CD (44, p<0.001), UC (47, p=0.042) and pouchitis (43, p=0.036). Multivariate discriminant analysis predicted HC, CD, UC and pouchitis group membership with high sensitivity and specificity. The levels of medium-chain fatty acids (MCFAs: pentanoate, hexanoate, heptanoate, octanoate and nonanoate), and of some protein fermentation metabolites, were significantly decreased in patients with CD, UC and pouchitis. Hexanoate levels were inversely correlated to disease activity in CD (correlation coefficient=−0.157, p=0.046), whereas a significant positive correlation was found between styrene levels and disease activity in UC (correlation coefficient=0.338, p=0.001). Conclusions: Faecal metabolic profiling in patients with IBD relative to healthy controls identified MCFAs as important metabolic biomarkers of disease-related changes. Trial Registration No: NCT 01666717.